Double poling in cross-country skiing: Biomechanical and physiological analysis of sitting and standing positions - Lund Ohlsson, M. (Mid Sweden University, Faculty of Human Sciences, Department of Health Sciences, 2018)
Double poling (DP) is a sub-technique in cross-country skiing that has increased in interest over the last decades, e.g. athletes in cross-country skiing have increased their utilisation of double poling during competitions. In cross-country sit-skiing athletes with impairments in legs and/or trunk sit in a sledge and utilise DP to propel themselves. Technique (i.e. movement pattern) is one key factor determining performance but also a factor that may affect the risk of overuse injuries in sports.